Development of calcium phosphates from waste resources and fabrication of calcium phosphate-chitosan composites - Nigar, Farah (2023)
Biowastes from agriculture, sewage, household wastes and industries comprise promising resources to produce biomaterials whilst reducing environmental impact. This study focused on utilising waste-derived materials (i.e., eggshells as calcium source, struvite as phosphate source and CH3COOH as dissolution media) to produce value-added products (i.e., calcium phosphate (CaP) derived biomaterials) using three different routes such as continuous flow hydrothermal synthesis, ball milling followed by sintering and flame spheroidisaion. Fabrication of composites (scaffolds and films) using commercial chitosan (Ch) and CaPs prepared using eggshells and struvite via three different methods mentioned above was also explored. The prepared materials were characterised via XRD, TGA/DSC, FEG-SEM, EDX, FTIR and TEM analysis.